2010
DOI: 10.12660/rbfin.v8n4.2010.1651
|View full text |Cite
|
Sign up to set email alerts
|

O Efeito Disposição na Indústria Brasileira de Fundos de Investimento em Ações

Abstract: The goal of this study is to test the disposition effect, the tendency of investors to sell winning investments too soon and hold losing investments too long, by analyzing all Brazilian equity fund portfolios from November 2003 to March 2008. The analysis based on the number of trades shows that equity funds are subject to the disposition effect. On the other hand, contrary to evidence from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Of all the analyzed funds, it was confirmed that, based on the average purchase price used to determine a loss or gain, managers sold more gainers than losers (demonstrating the disposition effect). When analyzing the monetary volume, despite the fact that there were a greater number of transactions with gainers, the volume is proportionally smaller (not demonstrating the disposition effect, backing the study by Tizziani et al (2010)). With regards to the performance of fund managers, approximately 78% showed signs of the disposition effect (referring to the number of transactions); by monetary volume, 57% of managers did not show signs of the effect, emphasizing the opposite result (Lucchesi, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 84%
See 2 more Smart Citations
“…Of all the analyzed funds, it was confirmed that, based on the average purchase price used to determine a loss or gain, managers sold more gainers than losers (demonstrating the disposition effect). When analyzing the monetary volume, despite the fact that there were a greater number of transactions with gainers, the volume is proportionally smaller (not demonstrating the disposition effect, backing the study by Tizziani et al (2010)). With regards to the performance of fund managers, approximately 78% showed signs of the disposition effect (referring to the number of transactions); by monetary volume, 57% of managers did not show signs of the effect, emphasizing the opposite result (Lucchesi, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 84%
“…In the behavioral finance field, the disposition effect (the tendency to sell gainers faster than losers) directly influences the behavior of the investor/manager and the pricing of assets in the market (Tizziani et al, 2010). The hypothesis that the proportion of realized gains would be greater than that of losses in the market was tested using the Odean method (1998) (Odean apud Tizziani et al, 2010). The method consists of monthly analyses of the portfolio to identify how often gains and losses are sold when compared to their respective opportunities to be realized (Tizziani et al, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 1994, investment funds were merely short term investment mechanisms (VARGA; WENGERT, 2011). According to Tizziani et al (2010) this growth is grounded on the continuity of the Real Economic Reform Plan, in parallel to control of inflation and foreign debt.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tizziani et al (2010), investment allocations are also defined by investor behavior. When faced by decisions involving risk, investors will tend to adopt irrational behaviors, contradicting the theory of expected utility (KAHNEMAN;TVERSKY, 1979).…”
Section: Introductionmentioning
confidence: 99%